2011
DOI: 10.1007/s11249-011-9824-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Friction Modulation on the Reconstructed Au(111) Surface

Abstract: Friction between a nanoscale tip and a reconstructed Au(111) surface is investigated both by atomic force microscopy (AFM) and molecular statics calculations. Lateral force AFM images exhibit atomic lattice stick-slip behavior with a superstructure corresponding to the herringbone reconstruction pattern. However, the superstructure contrast is not primarily due to variations in the local frictional dissipation (which corresponds to the local width of the friction loop). Rather, the contrast occurs primarily be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Also, in the case of the PtSi-tip a further modulation of the friction signal was observed that has been attributed in Ref. [23] to the Herringbone reconstruction of the Au(111) surface. In our statistical analysis, the presence of the Herringbone reconstruction resulted in a splitting of the PSD-peak, into two symmetrical peaks around the value corresponding to the interatomic distance of Au atoms in the [110] direction.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Also, in the case of the PtSi-tip a further modulation of the friction signal was observed that has been attributed in Ref. [23] to the Herringbone reconstruction of the Au(111) surface. In our statistical analysis, the presence of the Herringbone reconstruction resulted in a splitting of the PSD-peak, into two symmetrical peaks around the value corresponding to the interatomic distance of Au atoms in the [110] direction.…”
Section: Discussionsupporting
confidence: 59%
“…4(d), 6(a) and 6(b) the maximum in the PSDfunctions are also found to split into two equidistant peaks with corresponding wavelength-values  3 = 0.277 nm and  1 = 0.312 nm, respectively. We attribute these peaks to the herringbone reconstruction of the Au(111) surface and the resulting different tilt angles of the fcc and hcp domains with respect to the unreconstructed surface [23]. For the Pt-coated tip three main characteristic wavelengths can be determined [14].…”
Section: Resultsmentioning
confidence: 99%
“…However, this does not directly answer the question of where the modulated potential comes from. Initial work has been done by Li et al [58] to explain the friction offset modulation on a reconstructed Au (111) surface using MD simulation. The fully atomistic model revealed that the cause of the friction modulation is not the tiny rumpling in the normal direction, but rather can be attributed to the transitions from face-centered-cubic (FCC) to hexagonal-closepacked (HCP) structure on the surface.…”
Section: Friction Modulation Due To Surface Reconstructionmentioning
confidence: 99%
“…The peak in the PSD functions was also found to split into two equidistant peaks at F n = 10 nN, with corresponding wavelength values λ 3 = 0.277 nm and λ 1 = 0.312 nm, respectively. These peaks may correspond to the herringbone reconstruction of the Au(111) surface and the resulting different tilt angles of the fcc and hcp domains with respect to the unreconstructed surface [30]. AFM scratch testing was used to demonstrate the transitions between different wear regimes on Au(111) during single-asperity sliding contact.…”
Section: Contact and Fracture Mechanicsmentioning
confidence: 99%